Benchmarking for improving the quality of quality assurance institutions (LPM) in managing quality standards tri dharma of higher education - Fitriyani, Zenita Afifah; Dewi, Yuni Rosita (Institute of Computer Science (IOCS), 2024)
The aim of this research is to improve the quality of quality standards, especially in the field of the Tri Dharma of Higher Education through the Benchmarking program. The research method used was a qualitative method with data analysis techniques using PDCA analysis. The research informant was BPM UNISMA. The data collection techniques used were observation, interviews and discussions. The results of this research are that by using PDCA analysis, the results obtained are first, the formation of the organizational structure of GPM at the faculty level and UPM at the study program level, second, the involvement of GPM and UPM in conducting Internal Quality Audits (AMI), and third, the scheduling of RTM at the faculty and university level, so that It is hoped that this research can help improve university quality standards, especially in the Tri Dharma of Higher Education field.